Ammonia‐free natural rubber latex photo‐resin for sustainable 3D printing of highly stretchable and tough elastomers - Oliyad Dibisa; Allen Jonathan Román; Hannah Cabush; Grace O'Brien; Xiao Kuang; Tim A. Osswald (SPE Polymers)
Abstract Vat photopolymerization (VPP) is one of the most successful additive manufacturing modalities, offering high printing resolution and a wide selection of photo‐resins for applications in aerospace, electronics, soft robotics, and biomedical devices. However, conventional photo‐resins, primarily derived from fossil resources, present sustainability challenges. They often rely on short‐chain oligomers that form brittle, dense polymer networks, limiting their performance in high‐demand applications, especially for elastomeric materials. In this study, we developed an ammonia‐free natural rubber latex‐based photo‐resin featuring an ultra‐high molecular weight polymer with low viscosity (<10 Pa·s) and rapid curing speed (~11 s, corresponding to gelling point), making it highly suitable for VPP. The printed green parts underwent a two‐step process of crosslinking and coagulation, resulting in semi‐interpenetrating polymer networks with unique structural properties. Two curing intensities were investigated: 18 and 35 mW/cm2. Lower intensity resulted in lower 9×10−5mol/cm3 in crosslinked density and higher intensity, 1.4×10−4mol/cm3 in crosslink density. We systematically investigated multiscale structure–property relationships using spin–lattice (T1) and spin–spin (T2) relaxation analysis via inversion recovery and Carr‐Purcell‐Meiboom‐Gill. 18 mW/cm2 with 30 s of curing and drying resulted in two regimens of motion for Rubber polymer with intermediate crosslinking density and intermediate entanglements dominating the network. Also, 35 mW/cm2 with 30 s of curing and drying resulted in two regimes of Rubber polymer: however, one with a higher crosslinked and a mobile polymer phase. Optimized curing parameters enabled the fabrication of highly stretchable elastomers with 5–7.8 MPa tensile strengths and breaking strains of 750%–900%. These results highlight the potential of biomass‐based photo‐resins to advance sustainable 3D printing technologies. Furthermore, we demonstrated the feasibility of this formulation by printing complex geometries using a commercially available SLA printer. Highlights Ammonia‐free latex resin cures rapidly at <10 Pa·s for sustainable 3D printing. NMR reveals distinct rubber motions under 18 versus 35 mW/cm2 curing. 35 mW/cm2 raises crosslink density to 1.4 × 10−4 g/mol for tougher parts. Printed elastomers achieve 5–7.8 MPa and 750%–900% strain in minimal time. Complex 3D prints validated on a standard Form 2 SLA printer.